Caregiver and community insights on coping strategies used by adolescents living in conflict-affected communities. Issue 9 (2nd September 2018) - Cherewick, Megan; Glass, Nancy
ABSTRACT: The aim of this qualitative study was to provide a context-specific understanding of adolescent (10–15 years of age) exposure and coping with trauma from the perspective of mothers/female caregivers and key informants in rural conflict-affected villages. Focus groups were conducted with mothers/female caregivers (4 groups with total participants n  = 26) and interviews were conducted with key informants ( n  = 9) in four villages in the Walungu Territory, Eastern Democratic Republic of Congo. Focus group and interview guides were designed to elicit responses by participants on adolescent exposures to trauma and coping strategies. A grounded theory approach was used to identify emergent themes. Mothers/female caregivers and key informants reported use of both cognitive and behavioural coping strategies by adolescents. Cognitive coping strategies included avoidance and trying to forget. Behavioural strategies included self-imposed isolation, risk-taking and social-support-seeking behaviours. Findings indicated community social support was a critical resource for adolescents, particularly for adolescents that did not have adequate support from their family. Supporting positive peer, family and community relationships can help prevent risk-taking behaviours and teach positive coping strategies to break a cycle of violence reported in these communities. Recommendations for gender-specific intervention programming are highlighted. Abbreviations: DRC: Democratic Republic of Congo; PAIDEK: Programme d'Appui aux Initiatives Economiques; PFP: Pigs for Peace; RFR: Rabbits for Resilience